Pemanfaatn Platform Merdeka Mengajar Dalam Perencanaan Kurikulum Di Sekolah Dasar Negeri 01 Bambu Apus - Kamil, Naya Aulia (BADA’A: Jurnal Ilmiah Pendidikan Dasar, 2025)
The transformation of education in Indonesia through the implementation of the Merdeka Curriculum emphasizes the importance of student-centered learning and the continuous professional development of teachers. In this context, the use of technology becomes crucial to support adaptive and innovative learning processes. One of the initiatives introduced by the Ministry of Education, Culture, Research, and Technology is the Merdeka Mengajar Platform (PMM), which is designed to assist teachers in accessing learning materials, engaging in self-paced training, and sharing best practices in teaching.